The Voice of Transition: Linguistic and Cultural Reflections in Labeed ibn Rabi’ah’s Al-Mu’allaqah - Dahami, Yahya Saleh Hasan (UIN Sunan Gunung Djati Bandung, 2024)
This study aims to analyze the linguistic and cultural aspects of Labeed ibn Rabi’ah's Mu’allaqah, focusing on the moral and social values of pre-Islamic Arab society. Using a qualitative-descriptive approach with textual analysis, the research explores how Labeed's use of metaphor, rhythm, and rhetoric in classical Arabic reflects the cultural and emotional landscapes of his time. The study highlights the poet's mastery in describing places, which not only represent geographical locations but also convey themes of loss, change, and the passage of time. Through detailed descriptions of places like Mena, Al-Ghoul, and Al-Maqam, Labeed illustrates the transient nature of life and the absence of the once-vibrant communities tied to these locations. The findings emphasize the originality and impact of Labeed's work on classical Arabic poetry, contributing to the moral and cultural framework of pre-Islamic Arabia. This study further underscores the importance of Labeed’s poetic contributions, offering valuable insights into the linguistic richness and philosophical dimensions of Arabic poetry. The research also calls for further exploration of classical Arabic texts to deepen the understanding of their cultural significance and linguistic beauty.